O SEBRAE e o desenvolvimento econômico de Roraima: o papel desempenhado pelo Serviço Brasileiro de Apoio às Micro e Pequenas Empresas no desenvolvimento econômico e no fortalecimento empresarial de Boa Vista (1979-2015) - Galvão, Adailton Mendes (2015)
Identifying the Brazilian Support Service for Micro and Small Companies as an important agent to represent the state in offering to micro-companies the necessary infrastructure to develop and create more jobs and income through entrepreneurship, this research aims to identify relationships between economic and business strengthening in Roraima, through the actions sponsored by Sebrae throughout the state extension and especially the activities undertaken in the capital Boa Vista. The study searched scientific background in theories that address economic development, entrepreneurship, and state intervention in the economic structure. To promote the research, it was used as methodology, survey and bibliographical organization through several classic and contemporary authors on the topics, especially the theories proposed by Celso Furtado, Amartya Sen and Joseph Schumpeter and field research . The field research sought main character in collecting primary and secondary data qualitatively as well as quantitative data that helped strengthen and enrich the content of the proposed study. Subsequently, the data was processed and identified the problem and the hypotheses on the subject. It was also identified in the survey, the existence of places of business clustering by region, which has character of economic strengthening in regions, addressed. Another great relevance point was targeting Sebrae’s strategic plans of and its diversified and regionalized activities, giving autonomy to its regional units, which characterized Sebrae Roraima, the change in strategic focus, before only in the state capital, also to other cities in the state, supporting the strengthening of various economic segments yet to be exploited for development purposes.